Overweight/obesity in adolescents from Santa Maria, Brazil: prevalence and associated factors.DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n5p517 - Felipe Fossati Reichert; Roselaine Ruviaro Zanini; Paola Marques Duarte; Daniela Lopes dos Santos; Felipe Vogt Cureau (Universidade Federal de Santa Catarina, 2012)
Obesity is a worldwide epidemic that keeps on rising among children and adolescents from several countries. The purpose of this study was to verify the prevalence of overweight/obesity and its correlates in adolescents enrolled in the 1st year of high school in the municipality of Santa Maria, state of Rio Grande do Sul, Brazil. A cross-sectional, school-based, study was performed during the second semester of 2008. Adolescents aged 14 to 18 years old responded to a questionnaire and had their body mass and stature measured. The prevalence of overweight and obesity was defined according to the Brazilian reference for body mass index in adolescents. Correlates of overweight/obesity were determined by Poisson regression. The sample included 424 adolescents (54.7% boys) with mean age of 15.7 years (±0.89). The prevalence of overweight/obesity was 23.8% (95%CI; 19.75-27.85). After adjusting for potential confounding factors, the following variables were associated with overweight/obesity: sex (PR=2.45; 95%CI 1.63-3.68), having been dismissed from physical education classes (PR=2.73; 95%CI 1.88-3.95) and having a good relationship with classmates (PR=1.57; 95%CI 1.12-2.19). It was concluded that the prevalence of overweight/ obesity in this sample was high, prompting the need for preventive programs of excessive weight in this age group.